FORMULATION IN VITRO AND IN VIVO EVALUATION OF CEFUROXIME AXETIL FLOATING TABLETS USING NATURAL GUMS: Pharmaceutical Science-Pharmaceutics - SWAPNA R; BASAVA RAJU D; P. SHAILAJA (International Journal of Life Science and Pharma Research, 2019)
Floating tablets of Cefuroxime Axetil were prepared using Albizia gum, Dammar gum and Moi gum as polymers for controlling the drug release. Cefuroxime Axetil is a poorly water-soluble drug (second-generation cephalosporin) and its bioavailability is very low. The rate of absorption and the extent of bioavailability for such insoluble drug are controlled by the rate of dissolution in the gastrointestinal fluids. Two types of diluents were used and the drug release was compared. Pure drug and optimized formulation were subjected to the drug excipient compatibility studies using FTIR and DSC. The studies revealed that there was no interaction between the drug and excipients. In order to increase the drug release, channeling agents were introduced namely Lactose and DCP. Lactose is water soluble diluent and DCP is water insoluble diluent. All the formulations were taken and studied for the precompression parameters and found that they were within the limits. Precompression parameters were performed to all the formulations and were found to be in the acceptable limit which ensures the good flow properties. Formulation F4CADL containing gum dammar and lactose as channeling agent showed good results when compared with other formulations. The floating lag time of the optimized formulation was very short and the percentage of drug release at the end of 12 hours was found to be high. The drug release kinetics revealed that F4CADL follows KorsmeyerPeppas and the mechanism was non-fickian diffusion. Optimized formulation was selected for in vivo studies by using albino rabbits. It was found that the tmax was extended for prolonged period of time